Symptomatic Mullerian Duct Cyst in a Male Infant - Chinya, Abhishek (APSP J Case Rep, 2016)
Symptomatic Mullerian duct cyst is a rare entity in children. A 9-month-old male infant presented with bowel and urinary obstructive symptoms. Imaging investigations revealed a cystic mass in the rectovesical pouch compressing bladder neck and rectum. At laparotomy, a Mullerian duct cyst was found. Most of the cyst was excised and the remaining cyst mucosa was cauterized. The child improved thereafter.